[Myvatn From Top of Hverfjall] - Streng, Evelyn Fiedler (1975)
Photograph of Myvatn from the top of Hverfjall. The large lake is surrounded by green and forested lands. A single mountain is sat in the distance at the center of the photograph. Clouds cover the sky above, casting shadows along the ground.